Age and gender differences in employee cyberloafing behavior - Ahmad, Aminah; Omar, Zoharah (2016)
Cyberloafing at the workplace, a form of deviant behavior, refers to the use of organization’s Internet access by employees during work for non-work purposes. Recently, researchers have an increased interest in cyberloafing on the job among employees as they realize the negative outcomes of this behavior. This study examined whether there were differences in cyberloafing among younger and older employees as well as males and females. Using survey questionnaires, data were gathered from 260 Malaysian employees from a public sector organization. We found that irrespective of age, males engaged in cyberloafing more than females. Implications for organizations and research are presented.